Milk Emulsions: Structure and Stability - Katja Braun; Andreas Hanewald; Thomas A. Vilgis (Foods, 2019)
The main aim of this research is to investigate the characteristics of milk and milk proteins as natural emulsifiers. It is still largely unclear how the two main fractions of the milk proteins behave as emulsifier in highly concentrated emulsions. The surface-active effect of these is determined experimentally for emulsions with a high oil content (φ > 0.7), in this case fully refined rapeseed oil. Recent publications have not yet sufficiently investigated how proteins from native milk behave in emulsions in which a jamming transition is observed. In addition, scientific measurements comparing fresh milk emulsions and emulsions of dried milk protein powders based on rheological and thermal properties are pending and unexamined. The emulsions, prepared with a rotor-stator disperser, are investigated by their particle size and analysed by microscopy, characterised by their rheological properties. The behaviour under shear is directly observed by rheo-optical methods, which enables the direct observation of the dynamic behaviour of the oil droplets undergoing a size selective jamming transition. For a better understanding of the contributions of the different emulsifying proteins, oil-in-water emulsions have been prepared by using whey protein isolates and sodium casinates. Their different role (and function) on the interface activity can be assigned to the droplet sizes and mechanical behaviour during increasing shear deformation. In addition, solid (gelled) emulsions are prepared by heating. It is shown that the cysteine-containing whey proteins are mainly responsible for the sol−gel transition in the continuous water phase and the formation of soft solids.